State of the world 2011 : innovations that nourish the planet : a Worldwatch Institute report on progress toward a sustainable society - Starke, Linda (State of the world ;, 2011)
"Known for tackling the most pressing issues that face our world, the Worldwatch Institute has dedicated the 2011 edition of its flagship report to a compelling look at the global food crisis, with particular emphasis on what innovators globally can do to help solve a worldwide problem. State of the World 2011 not only introduces us to the latest agro-ecological innovations and their global applicability but also gives broader insights into issues including poverty, international politics, and even gender equity."--Publisher description